Personal and complex: The needs and experiences related to technology use for people living with dementia. (July 2022) - Liddle, Jacki; Worthy, Peter; Frost, Dennis; Taylor, Eileen; Taylor, Dubhglas; Beleno, Ron; Angus, Daniel; Wiles, Janet; Angwin, Anthony; ,
Background: With increasing focus on living well with dementia, technology has been identified as having potential benefits for safety, independence and wellbeing. Despite a large growth in specialised technology development, there has been limited uptake. There is a need to understand the current use and needs related to technology for people living with dementia and their care partners (informal carers). Methods: As part of a participatory design study, a qualitative inquiry into technology experiences and needs was undertaken within an interpretive description approach. A cross-disciplinary team including living experience experts (people living with dementia, unpaid care partners) was involved. Semi-structured interviews, including sharing technology locations and supports, were conducted, audio-recorded and transcribed. Key aspects of the technology use experience were constructed. Findings: Thirteen people living with dementia and 21 care partners participated in the study. Two core aspects of technology use were identified: Lots of moving parts: the complex context, and A technology cycle: the use and non-use. The findings indicated that the context involved an individual configuration of multiple factors including the user, their technology identity, their supporters, the technology and the environment. The experience is underpinned by shifting foundations created by constantly changing technologies and user characteristics. The cycle of use and non-use identified the processes required to maintain technology engagement. Conclusion: The use of technology for people living with dementia is complex and personal. Future technology development, policies and practices need to consider this complexity and the effort required to keep using technology to realise the benefits.